DETERMINATION OF OPTIMAL PARAMETERS FOR SYNTHESIS OF SILVER NANOPARTICLES STABILIZED WITH POLYETHYLENE GLYCOL - A.V. Blinov (Tver State University, 2021)
Within the framework of this work, the results are presented of a study of the effect of the concentrations of the stabilizer and precursor on the synthesis of silver nanoparticles. Silver nitrate was used as a precursor, and polyethylene glycol with a molecular weight from 200 to 600 Da was used as a stabilizer. The synthesis was carried out by the method of chemical reduction in an aqueous medium. The obtained samples were investigated by photon correlation spectroscopy and spectrophotometry. The presence of a characteristic absorption band at 400 nm in the absorption spectra of all samples of nanosized silver stabilized with polyethylene glycol was established, which is due to the appearance of surface plasmon resonance in metallic silver nanoparticles. It was also found that at the highest and lowest concentration of the stabilizer, equal, respectively, 0,005 and 0,1 mass. %, the formation of large silver particles with an average hydrodynamic radius from 132 to 1900 nm is observed in the reaction system. As a result, the optimal parameters for the synthesis of aggregatively stable silver nanoparticles were determined: the concentration of silver nitrate CM(AgNO3)=0,05 M and the concentration of polyethylene glycol equal to 0,01 – 0,05 %. Computer quantum-chemical modeling is carried out. It is found that the interaction of the silver atom with the terminal hydroxogroup in the polyethylene glycol molecule in the elementary act of interaction during the stabilization of silver nanoparticles by this polymer is energetically advantageous. This type of interaction is characterized by an absolute chemical hardness equal to η=0,146, and an internal energy of E=–2048,34 kcal / mol.